(untitled) (Boletin Médico de Postgrado, 2020)
Succinylcholine is a depolarizing neuromuscular drug generally used in the context of rapid sequence intubation indicated in patients in whom it is necessary to secure the airway in less than sixty seconds. A descriptive cross-sectional study was conducted in order to determine the duration of neuromuscular blockade with succinylcholine and plasma cholinesterase levels in septic patients admitted at Hospital Central Universitario Dr. Antonio Maria Pineda. A sample of 30 patients with sepsis were studied, with a mean age of 49.6 ± 17.4 years, predominantly male (70%). The main indication for abdominal surgery was intestinal obstruction (36.6%) and secondary peritonitis (23.3%). Diminished values of plasma cholinesterase were recorded in 42.8% of men and 33.3% of women; mean plasma levels were 5554.1 ± 1220.5 U/L and 4770.1 ± 1627.4 U/L, respectively. Duration of neuromuscular blockade was longer in women (66.6%) with an average duration of 14.4 ± 5.1 min and 9.4 ± 4.3 min for men. A poor correlation between cholinesterase plasmatic levels and duration as well as time of recovery of neuromuscular blockage was found. Prolonged neuromuscular blockade is due to low cholinesterase activity after administration of succinylcholine and occurs in less than half of septic patients studied.